2021
DOI: 10.3390/cancers13174388
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Optical Genome Mapping for the Assessment of Genomic Aberrations in Acute Lymphoblastic Leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is the most prevalent type of cancer occurring in children. ALL is characterized by structural and numeric genomic aberrations that strongly correlate with prognosis and clinical outcome. Usually, a combination of cyto- and molecular genetic methods (karyotyping, array-CGH, FISH, RT-PCR, RNA-Seq) is needed to identify all aberrations relevant for risk stratification. We investigated the feasibility of optical genome mapping (OGM), a DNA-based method, to detect these aberratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 43 publications
(52 reference statements)
5
58
0
4
Order By: Relevance
“…16,18 Following this finding the OGM analytical soft- this study. 16,18 Moreover, Lestringant et al also reported cross-contamination between samples, a problem we did not encounter. 16 Besides potentially missing important alterations, OGM sometimes also provides false-positive results.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…16,18 Following this finding the OGM analytical soft- this study. 16,18 Moreover, Lestringant et al also reported cross-contamination between samples, a problem we did not encounter. 16 Besides potentially missing important alterations, OGM sometimes also provides false-positive results.…”
Section: Discussionmentioning
confidence: 77%
“…This technology has already been applied to different cohorts of patients with hematological neoplasms with promising results. [15][16][17][18] Here, we examine the application of OGM for the genetic characterization of newly diagnosed ALL patients to determine whether this approach can eventually replace all, or part of, the current testing strategy. It is expected that OGM will not only lead to an improved detection rate of chromosome abnormalities but could also facilitate the identification of novel aberrations and contribute to the betterindividualized treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In a cohort of 12 pediatric ALL patients, Lühmann et al recently proved the feasibility of OGM in detecting relevant variants in ALL. 19 Preliminary OGM results for MDS and AML arising from MDS in 12 patients are available from Yang et al 16 In our study, bone marrow and peripheral blood samples from patients with AML and MDS with excessive blasts were analyzed by OGM. Routine analysis by karyotyping took place in parallel to OGM in order to assess the logistics and practicability of OGM as well as the concordance in this group of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Recent analysis showed a high concordance of OGM results compared to other cytogenetic methods in hematological malignancy genomes 14,16 and ALL patients. 18,19 In our study we asked in a proof-of-principle design, whether OGM can replace conventional cytogenetic diagnostics and provides additional information with potential impact on treatment in a clinical setting. Overall, 27 cases of AML and MDS were analyzed by OGM parallel to standard diagnostic workup, including conventional karyotyping, molecular diagnostics, such as multiplex PCR assays and FISH for some cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation